2007
DOI: 10.2174/092986707781058823
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Potential of the Growth-Inhibitory Actions of Vitamin D and Analogs

Abstract: 1alpha,25-Dihydroxyvitamin D(3) [1,25-(OH) (2)D(3)] can exert its biological actions through binding with the nuclear vitamin D receptor (VDR), a ligand-activated transcription factor. Next to control of bone and mineral homeostasis, these actions include an immunomodulatory effect and a potent growth-inhibitory, antiproliferative or prodifferentiating action on a wide variety of cell types. The molecular mechanisms underlying this antiproliferative action form an intriguing research topic and they remain, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 172 publications
(197 reference statements)
1
60
0
Order By: Relevance
“…In 1975, journals published only Ȃ100 articles per year that included the term vitamin D in the title or abstract; by 2007, the rate of publication had increased to 1400 articles per year. Another driving factor for this increased publication rate was the chemical synthesis by academic chemists and by 4 pharmaceutical companies of 2000 analogues of 1␣,25(OH) 2 D; most of these analogues were targeted toward selective responses in diseases such as osteoporosis, renal osteodystrophy, and psoriasis, and the authors reported their biological properties in a multitude of publications (8,26 Figure 2 emphasizes the structural differences between vitamins D 3 and D 2 and provides a clear description and comparison of the biological properties of these 2 key molecules. This figure shows that 1) vitamin D 3 is the only naturally occurring form of vitamin D in humans and other animals and 2) vitamin D 2 has only one-third the biological activity of vitamin D 3 in humans (7).…”
Section: Expansion Of Vitamin D Knowledgementioning
confidence: 99%
“…In 1975, journals published only Ȃ100 articles per year that included the term vitamin D in the title or abstract; by 2007, the rate of publication had increased to 1400 articles per year. Another driving factor for this increased publication rate was the chemical synthesis by academic chemists and by 4 pharmaceutical companies of 2000 analogues of 1␣,25(OH) 2 D; most of these analogues were targeted toward selective responses in diseases such as osteoporosis, renal osteodystrophy, and psoriasis, and the authors reported their biological properties in a multitude of publications (8,26 Figure 2 emphasizes the structural differences between vitamins D 3 and D 2 and provides a clear description and comparison of the biological properties of these 2 key molecules. This figure shows that 1) vitamin D 3 is the only naturally occurring form of vitamin D in humans and other animals and 2) vitamin D 2 has only one-third the biological activity of vitamin D 3 in humans (7).…”
Section: Expansion Of Vitamin D Knowledgementioning
confidence: 99%
“…Many epidemiological and animal studies indicate that the active vitamin D metabolite 1a, 25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) affords protection against colon cancer (Campbell and Adorini, 2006;Deeb et al, 2007;Eelen et al, 2007). A causal link between vitamin D deficiency and colon cancer has recently been considered probable by the International Agency for Research on Cancer (IARC, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In vivo studies have demonstrated inhibitory effects of calcitriol and its analogs on the growth of human PCa xenografts in immunocompromised mice causing significant reduction in tumor size and volume. 5,[11][12][13] Transgenic models of PCa have also been developed in animals to study the chemopreventive effects of calcitriol and its analogs.…”
Section: Introductionmentioning
confidence: 99%